Peran Gizi dan Istirahat dalam Menunjang Kesamaptaan Prajurit di Lapangan (Studi pada Prajurit TNI di Wilayah Sumatera Utara) - Putri, Anatasya; Sembiring, Zamalludin (Lembaga Yasin AlSys, 2025)
This study is motivated by the importance of physical and mental fitness as crucial aspects in supporting soldiers' operational readiness in the field, including the need for a balance between optimal nutritional intake and adequate rest. The purpose of this research is to analyze the role of nutrition and rest in supporting the physical fitness level of TNI soldiers in the North Sumatra region. A qualitative approach was used, with data collected through observation, interviews, and physical condition assessments of the soldiers. The results show that meeting the needs for balanced nutrition and sufficient rest has a significant relationship with soldiers' fitness levels. Soldiers with good dietary patterns and regular sleep schedules tend to exhibit higher physical performance, stronger immunity, and better emotional stability and cognitive function. Nutritional intake that includes macronutrients (carbohydrates, protein, healthy fats) and micronutrients (vitamins, minerals) is essential for maintaining physical and mental health. On the other hand, quality sleep of 7 to 9 hours per day plays a role in cell regeneration, immune system enhancement, and stress hormone regulation. The main challenges faced by soldiers include logistical constraints, extreme weather conditions, psychological pressure, and irregular rest periods. To address these issues, strategies such as the provision of nutritious ready-to-eat meals, portable rest facilities, and education on nutrition and sleep management can be applied. The conclusion of this study is that nutrition and rest are fundamental factors in maintaining the overall physical fitness of soldiers.